Profile of onychomycosis in dermatology outpatient department at Sanglah General Hospital Denpasar, Bali-Indonesia periods 2016-2017 - IGAA Dwi Karmila; Adeline Santoso (Explorer Front, 2018)
Introduction: Onychomycosis is a fungal infection of the nails that causes discoloration, thickening, and separation from the nail bed. Onychomycosis is caused by various organisms, most often dermatophytes of the genus Trichophyton. Other organisms include Candida, which is more common in fingernail infections and patients with chronic mucocutaneous candidiasis. Nondermatophyte molds are a less common cause in the general population. This study aimed to identify sex, age, classification, fungal culture, treatment, and incident of secondary infection in onychomycosis at Dermatology Outpatient Department at Sanglah General Hospital Denpasar Periods January 2016 – December 2017. Methods: Study design using descriptive retrospective model done by taking data from medical record in Dermatology Outpatient Department at Sanglah General Hospital Denpasar Periods 2016-2017. Result: There were 268 patients in Dermatovenereology Outpatient Department at Sanglah General Hospital Denpasar, 29 (10,82%) of whom were diagnosed with onychomycosis in Periods 2016-2017. According to age group, the most cases occur in 26-65 year age groups. Females were more frequently affected than males. The most classification finding is distal and lateral subungual onychomycosis and the most commonly isolated fungi were yeasts from the Candida species. The most commonly given therapy is a combination therapy of systemic antifungal with topical. Fluconazole is the most common drug that uses orally and ciclopirox as topical agent. Conclusions: Onychomycosis is one of the common fungal infection observed in patient attending dermatology outpatient department with the most classification finding is distal and lateral subungual onychomycosis. The most commonly isolated fungi were Candida sp.